Cracking method of high-alkalinity polysulfide rubber latex

By using a cracking agent composed of sodium sulfite, sodium bisulfite and sodium hydrosulfide to crack the high alkaline polysulfide rubber latex, the problems of frequent washing times and large wastewater discharge in the prior art are solved, and efficient polysulfide rubber production is achieved.

CN120365561APending Publication Date: 2025-07-25JINXI RES INST OF CHEM IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510435626.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The water washing process in the existing liquid polysulfide rubber production requires multiple water washing, resulting in large amounts of water and large wastewater discharge, increasing the burden of sewage treatment and operating costs, and at the same time, inefficient production efficiency.

Method used

The cracking agent composed of sodium sulfite, sodium bisulfite and sodium hydrosulfide is used to crack the high alkaline polysulfide rubber latex to reduce the number of washes, and control the reaction process to prepare polysulfide rubber with appropriate molecular weight.

Benefits of technology

The water consumption and wastewater discharge of the water washing process are reduced, process efficiency is improved, wastewater treatment costs are reduced, and overall production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of high-molecular polymer synthesis, and particularly discloses a cracking method of high-alkalinity polysulfide rubber latex, which comprises the following steps: S1, carrying out mother liquor separation on polysulfide rubber latex, and then washing for 0-2 times to obtain the high-alkalinity polysulfide rubber latex; and S2, cracking the high-alkalinity polysulfide rubber latex into liquid polysulfide rubber by using a cracking agent composed of sodium sulfite, sodium hydrogen sulfite and sodium hydrosulfide, wherein the molecular weight of the liquid polysulfide rubber is 1000-5000. Compared with the prior art, the cracking agent composed of sodium sulfite, sodium hydrogen sulfite and sodium hydrosulfide is adopted, high-alkalinity polysulfide rubber latex can be cracked, the washing frequency is reduced, the process efficiency is improved, and the overall polysulfide rubber production efficiency is indirectly improved; meanwhile, the wastewater discharge amount is reduced, and the subsequent wastewater treatment cost is reduced. The raw materials required by the cracking agent are easy to obtain and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer synthesis, and particularly relates to a method for cracking high-alkaline polysulfide rubber latex. Background Art

[0002] Liquid polysulfide rubber is usually synthesized by the following process route. First, sodium disulfide and bis(2-chloroethyl) formal monomer undergo a polycondensation reaction to generate a high-molecular-weight disulfide aqueous dispersion (i.e., polymerization latex). The polymerization latex is washed with water multiple times to remove excessive inorganic salts, and then sodium hydrosulfide and sodium sulfite are used to crack the high-molecular-weight disulfide polymer into small molecules to form a cracked latex. The cracked latex is acidified with dilute sulfuric acid and coagulated to generate liquid polysulfide rubber.

[0003] The existing water washing process for liquid polysulfide rubber is to put the polymerization latex into a mother liquor separation tank for natural sedimentation to separate the mother liquor. After that, the latex after separating the mother liquor is put into a water washing tank, water is added and stirred evenly, left to stand and settle, and the upper layer of waste water is discharged. The above water washing process is repeated until the polymerization latex is washed to a pH of 6-8 to complete the water washing process. To produce 1 ton of polysulfide rubber, about 40 tons of water washing waste water need to be discharged.

[0004] The existing water washing process requires multiple water washings, not only with a large amount of process water consumption, but also with a large amount of waste water discharge, increasing the burden of sewage treatment and the operating cost of the device. At the same time, due to multiple natural sedimentation processes, the process operation time is long and the production efficiency of the device is low. Summary of the Invention

[0005] In order to solve the above technical problems, the present invention provides a method for cracking high-alkaline polysulfide rubber latex. By improving the cracking agent, adjusting the cracking agent ratio and controlling the reaction process, the high-alkaline polysulfide rubber latex can be cracked, the number of water washings can be reduced, and polysulfide rubber with a suitable molecular weight can be prepared. The reaction is stable and the product quality is easy to control.

[0006] To achieve this technical purpose, the present invention adopts the following scheme: A method for cracking high-alkaline polysulfide rubber latex, comprising the following steps: S1. After the polysulfide rubber latex is separated from the mother liquor, it is washed with water 0-2 times to obtain high-alkaline polysulfide rubber latex; S2. The high-alkaline polysulfide rubber latex is cracked into liquid polysulfide rubber with a molecular weight of 1000-5000 by a cracking agent composed of sodium sulfite, sodium bisulfite and sodium hydrosulfide.

[0007] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention uses a cracking agent composed of sodium sulfite, sodium bisulfite and sodium hydrosulfide, which can crack high-alkaline polythiol rubber latex, reduce the number of water washing times, improve the process efficiency, and indirectly improve the overall production efficiency of polythiol rubber. At the same time, the waste water discharge is reduced, and the subsequent waste water treatment cost is reduced. The raw materials required for the cracking agent of the present invention are easily available and the cost is low.

[0008] Further, in step S1, the pH of the high-alkaline polythiol rubber latex is 8-13.

[0009] Further, in step S2, the mass ratio of the high-alkaline polythiol rubber latex, sodium sulfite and sodium bisulfite is 10:15-12:6-3; the mass of sodium hydrosulfide is 1%-4% of the high-alkaline polythiol rubber.

[0010] Further, in step S2, the reaction temperature for cracking the high-alkaline polythiol rubber latex is controlled between 75°C and 85°C, and the reaction time is controlled between 0.5 and 1 h.

[0011] Further, the specific steps of step S2 are: adding the high-alkaline polythiol rubber latex into a reactor, starting stirring, and heating the reactor; heating to 60-70°C, dropping a mixed solution of sodium sulfite and sodium bisulfite, and after the temperature is stable for 10-15 minutes, continuing to heat to 75-85°C, adding a sodium hydrosulfide solution, and continuously reacting for 0.5-1 hour.

[0012] Further, the concentration of sodium sulfite in the mixed solution is 220±20 g / L, the concentration of sodium bisulfite is 250±20 g / L, and it is dropped within half an hour; the concentration of sodium hydrosulfide is 400±20 g / L. Specific embodiments

[0013] In order to fully understand the purpose, features and effects of the present invention, the present invention will be described in detail by means of the following specific embodiments, but the present invention is not limited thereto.

[0014] The present invention provides a method for cracking high-alkaline polythiol rubber latex, comprising the following steps: S1. After the polythiol rubber latex is separated from the mother liquor, it is washed 0-2 times with water to obtain high-alkaline polythiol rubber latex, and the pH of the high-alkaline polythiol rubber latex is 8-13; The preparation and water washing process of the polythiol rubber polymer latex are both well-known methods. Refer to the second edition of "Synthetic Rubber Industry Handbook" edited by Zhao Xutao and Liu Dahua, published by Chemical Industry Press in 2006, pages 1181-1182. It will not be elaborated in this application.

[0015] S2. The high-alkaline polythiol rubber latex is cracked into liquid polythiol rubber with a cracking agent composed of sodium sulfite, sodium bisulfite and sodium hydrosulfide, and the molecular weight of the liquid polythiol rubber is 1000-5000.

[0016] Among them, the mass ratio of the highly basic polythiol rubber latex, sodium sulfite and sodium bisulfite is 10:15-12:6-3; the usage amount of sodium hydrosulfide is 1%-4% of the highly basic polythiol rubber.

[0017] Sodium sulfite and sodium bisulfite are used as a mixed solution. The concentration of sodium sulfite is 220±20 g / L, and the concentration of sodium bisulfite is 250±20 g / L; sodium hydrosulfide is used as a solution, and the concentration of sodium hydrosulfide is 400±20 g / L.

[0018] The reaction temperature for the cracking of the highly basic polythiol rubber latex is controlled between 75°C and 85°C, and the reaction time is controlled between 0.5 and 1 h.

[0019] The specific steps of step S2 are as follows: Add the highly basic polythiol rubber latex into the reactor, start stirring, and heat the reactor; raise the temperature to 60-70°C, and dropwise add the mixed solution of sodium sulfite and sodium bisulfite, and complete the dropping within half an hour. After the temperature is stable for 10-15 minutes, continue to raise the temperature to 75-85°C, add the sodium hydrosulfide solution, and continuously react for 0.5-1 hour.

[0020] After the cracking of the highly basic polythiol rubber latex, it needs to be acidified and washed with water to obtain polythiol rubber. The specific operations in the acidification and water washing processes are all prior arts and will not be elaborated here. Example 1

[0021] First, weigh 400 g of latex (the latex is washed once with water, and the pH is 9), 10 g of sodium hydrosulfide, 500 g of sodium sulfite, and 150 g of sodium bisulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex into the reactor, start stirring, and heat the reactor; raise the temperature to 60°C, dropwise add the mixed solution of sodium sulfite and sodium bisulfite. After the temperature is stable for 10-15 minutes; continue to raise the temperature to 80°C, add the sodium hydrosulfide solution, and continuously react for 0.5 hour. After the reaction is completed; through subsequent processes, the prepared polythiol rubber product is measured to have a molecular weight of 4023. Example 2

[0022] First, weigh 400 g of latex (the latex is washed twice with water, and the pH is 8), 10 g of sodium hydrosulfide, 480 g of sodium sulfite, and 120 g of sodium bisulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex into the reactor, start stirring, and heat the reactor; raise the temperature to 70°C, dropwise add the mixed solution of sodium sulfite and sodium bisulfite. After the temperature is stable for 10-15 minutes; continue to raise the temperature to 85°C, add the sodium hydrosulfide solution, and continuously react for 0.5 hour. After the reaction is completed; through subsequent processes, the prepared polythiol rubber product is measured to have a molecular weight of 3623. Example 3

[0023] First, weigh 400 g of latex (the latex is washed 0 times with water and has a pH of 13), 14 g of sodium hydrosulfide, 500 g of sodium sulfite, and 150 g of sodium bisulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex to the reactor, start stirring, and heat the reactor; heat up to 60 °C, and dropwise add the mixed solution of sodium sulfite and sodium bisulfite. After the temperature is stable for 10 - 15 minutes; continue to heat up to 75 °C, add the sodium hydrosulfide solution, and continue the reaction for 1 hour. After the reaction is completed; through subsequent processes, the prepared polythiirubber product has a measured molecular weight of 2544. Example 4

[0024] First, weigh 400 g of latex (the latex is washed 1 time with water and has a pH of 10), 15 g of sodium hydrosulfide, 530 g of sodium sulfite, and 150 g of sodium bisulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex to the reactor, start stirring, and heat the reactor; heat up to 60 °C, and dropwise add the mixed solution of sodium sulfite and sodium bisulfite. After the temperature is stable for 10 - 15 minutes; continue to heat up to 80 °C, add the sodium hydrosulfide solution, and continue the reaction for 0.5 hour. After the reaction is completed; through subsequent processes, the prepared polythiirubber product has a measured molecular weight of 2236.

[0025] Comparative Example 1 First, weigh 400 g of latex (the latex is washed 1 time with water and has a pH of 9), 10 g of sodium hydrosulfide, and 600 g of sodium sulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex to the reactor, start stirring, and heat the reactor; heat up to 60 °C, and dropwise add the sodium sulfite solution. After the temperature is stable for 10 - 15 minutes; continue to heat up to 80 °C, add the sodium hydrosulfide solution, and continue the reaction for 0.5 hour. The raw materials directly polymerize in the equipment, and the reaction fails.

[0026] Comparative Example 2 First, weigh 400 g of latex (the latex is washed 1 time with water and has a pH of 9), 10 g of sodium hydrosulfide, 350 g of sodium sulfite, and 350 g of sodium bisulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex to the reactor, start stirring, and heat the reactor; heat up to 60 °C, and dropwise add the mixed solution of sodium sulfite and sodium bisulfite. It is found that flocculants gradually appear in the flask, and a large amount of flocculants appear after the dropping is completed, and the reaction fails.

[0027] Comparative Example 3 First, weigh 400 g of latex (the latex has been washed once with water and has a pH of 9), 10 g of sodium hydrosulfide, 500 g of sodium sulfite, and 100 g of potassium bisulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex to the reactor, start stirring, and heat the reactor; heat up to 70 °C, dropwise add the mixed solution of sodium sulfite and potassium bisulfite, and wait for the temperature to stabilize for 10 - 15 minutes; then continue to heat up to 85 °C, add the sodium hydrosulfide solution, and continue the reaction for 0.5 hours until the reaction ends; then through subsequent processes, the prepared polythiurane rubber product is measured to have a molecular weight of 1254.

[0028] Comparative Example 4 First, weigh 400 g of latex (the latex has been washed 4 times with water and has a pH of 7), 10 g of sodium hydrosulfide, and 600 g of sodium sulfite to prepare the raw materials. In a 2000 mL four-necked flask equipped with a stirrer, a thermometer, and a dropping funnel device, add the latex to the reactor, start stirring, and heat the reactor; heat up to 70 °C, dropwise add the sodium sulfite solution, and wait for the temperature to stabilize for 10 - 15 minutes; then continue to heat up to 85 °C, add the sodium hydrosulfide solution, and continue the reaction for 0.5 hours until the reaction ends; then through subsequent processes, the prepared polythiurane rubber product is measured to have a molecular weight of 3856.

[0029] The Shore A hardness of the polythiurane rubber obtained from the examples and comparative examples was measured according to the standard GB / T531.1 - 2008, and the tensile strength and elongation at break were measured with reference to the standard GB / T528 - 2009. The results are shown in the following table.

[0030]

[0031] It can be seen from this that the cracking agent composed of sodium sulfite, sodium bisulfite, and sodium hydrosulfide in the present invention can crack the high-alkaline polythiurane rubber latex. Compared with the original cracking process, the properties of the prepared polythiurane rubber are equivalent, but the water consumption in the water washing process is greatly reduced, the number of water washing times is reduced, the process efficiency is improved, and the overall production efficiency of polythiurane rubber is indirectly improved.

[0032] Finally, it should be noted that: the above-listed are only the preferred embodiments of the present invention. Of course, those skilled in the art can make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and its equivalent technologies, they should all be considered as the protection scope of the present invention.

Claims

1. A cracking method for highly basic polythiol rubber latex, characterized in that, It includes the following steps: S1. After the polysulfide rubber latex is separated from the mother liquor, it is washed with water 0 to 2 times to obtain a highly alkaline polysulfide rubber latex; S2. The highly alkaline polysulfide rubber latex is cracked into liquid polysulfide rubber with a cracking agent composed of sodium sulfite, sodium bisulfite and sodium hydrosulfide, and the molecular weight of the liquid polysulfide rubber is 1000 to 5000.

2. The cracking method of the highly basic polythiol rubber latex according to claim 1, characterized in that, In step S1, the pH of the highly alkaline polysulfide rubber latex is 8 to 13.

3. The cracking method of the highly basic polythiol rubber latex according to claim 1, characterized in that, In step S2, the mass ratio of the highly alkaline polysulfide rubber latex, sodium sulfite and sodium bisulfite is 10:15 to 12:6 to 3, and the mass of sodium hydrosulfide is 1% to 4% of the highly alkaline polysulfide rubber.

4. The cracking method of the highly basic polythiol rubber latex according to claim 1, characterized in that, In step S2, the reaction temperature for cracking the highly alkaline polysulfide rubber latex is controlled between 75°C and 85°C, and the reaction time is controlled between 0.5 and 1 h.

5. The cracking method of the highly basic polythiol rubber latex according to claim 1, characterized in that, The specific steps of step S2 are as follows: Add the highly alkaline polysulfide rubber latex into the reactor, start stirring, and heat the reactor; heat up to 60 to 70°C, dropwise add the mixed solution of sodium sulfite and sodium bisulfite, and after the temperature is stable for 10 to 15 minutes, continue to heat up to 75 to 85°C, add the sodium hydrosulfide solution, and continuously react for 0.5 to 1 hour.

6. The cracking method of the highly basic polythiol rubber latex according to claim 5, characterized in that, The concentration of sodium sulfite in the mixed solution is 220 ± 20 g / L, the concentration of sodium bisulfite is 250 ± 20 g / L, and it is added dropwise within half an hour; the concentration of sodium hydrosulfide is 400 ± 20 g / L.

Citation Information

Cited By

  • Polythionocarbamate sealant and preparation method thereof

    CN122037113A